Challenges to cross-sectoral care experienced by professionals working with patients living with low back pain: a qualitative interview study - Lisbeth Petersen; Regner Birkelund; Berit Schiøttz-Christensen (BMC, 2020)
Abstract Background While interdisciplinary, cross-sectoral collaboration promotes the effectiveness of rehabilitation programmes for persons with low back pain, challenges remain for this process. Few studies have explored challenges to cross-sectoral care as experienced by all the involved professionals across sectors during a course of treatment. The aim of this study was to explore challenges to cross-sectoral care as experienced by professionals involved in the course of treatment for patients with low back pain. Method This semi-structured, qualitative interview study included 28 health care professionals and 8 social workers who interacted with patients with low back pain. A systematic text condensation method was used to analyse data. Nvivo was used to structure and thematise the interview data. Results Professionals expressed challenges in relation to a lack of collaboration, knowledge sharing and acknowledgement of one other and they appeared to differ in their approach to patients with pain or patients with limited function. Additional challenges included time constraints, availability and subjective approaches to managing guidelines for low back pain. A lack of a common information technology (IT) registration system and limited knowledge of the work of other professions disrupted knowledge sharing among sectors. Discussion The different approach to patients with pain or patients with limited function challenged mutual understanding and collaboration among professionals. The lack of mutual understanding and knowledge of each other's work appeared to create an environment of disrespect and distrust among professionals that generated feelings of a lack of acknowledgement from other health care professionals. Conclusion To provide cross-sectoral care, we must ensure that professionals work together towards transparent and informed transitions from one sector to the next. This study contributes to the existing literature by presenting challenges to cross-sectoral care that are experienced by the diverse groups of professionals involved in a course of treatment for patients with low back pain.